Assembleia de Deus - Ministério Madureira Campo de Carapicuíba-SP: segredo do negócio - Silva, Sergio Ribeiro (2023)
The present work aims to study the process of growth of the evangelical church Assembléia de Deus Ministério Madureira in Campo de Carapicuíba, seeking in a case study, to reveal how this process took place. For this, we survey the history of this institution, in important moments from the beginning to the present day, analyzing the concepts of empowerment, pentecostalism, practices and cultural traditions that the leadership exerts on pastors, missionaries, evangelists and its members, incorporating them like a routine and making them part of rituals. Present the structure for the constitution of a temple, the path taken by a member to occupy a ministerial position, and how the elections work to choose a new board and, beyond that, find out if there is a business secret in the evangelical church Assembléia de Deus Ministério Madureira in Campo de Carapicuíba. For this work, we resorted to classic Sociology authors such as Marx (2010), Weber (2004), Bourdieu (2009), Guerreiro Ramos (1946) among others, as well as scholars of the subject such as Rotterdam (2009), Alencar (2012, 2013, 2014), Mariano (2004), Correa (2012, 2014), Almeida and Lobo (2014), Carreiro (2014) among others